A new heat transfer model for single U-pipe ground heat exchanger. (25th May 2019) - Wang, Chang-Long; Li, Huan; Huang, Zhi-Jia; Lu, Yue-Hong; Huang, Xin-Jie; Gan, Lin
Highlights: A new heat transfer model for single U-pipe ground heat exchanger is proposed. The model matches with experiment data especially during short time and interruption. Four kinds of errors of the model are basically smaller than those of other models. The absolute errors are within 0.23 °C except during early 4 h and the interruption. Abstract: A new heat transfer model for single U-pipe ground heat exchanger is proposed, including two parts: firstly, the single U-pipe is simplified as an equivalent pipe, and a 1D numerical model is established to calculate the average fluid temperature and borehole wall temperature; then, considering the nonlinear distribution of the fluid temperature based on a quasi-3D model, the inlet and outlet fluid temperatures of the U-pipe are derived as functions of the average fluid temperature and borehole wall temperature, respectively. To verify the feasibility of the proposed model, it is applied to an uninterrupted sandbox test and an interrupted sandbox test, and the calculated inlet and outlet fluid temperatures are compared with experimental data and the results of other models. Compared with other models, the fluid temperatures calculated by the proposed model are in better agreement with the experimental data especially during the short time and the interruption time, and four kinds of errors of the proposed model are basically smaller. The absolute errors of the fluid temperatures calculated by the proposed model are within 0.23 °C except during the early 4 h and the interruption time. The results show that the proposed model has high precision with short calculation time.